2017
DOI: 10.1039/c7sc03631k
|View full text |Cite|
|
Sign up to set email alerts
|

A benzylic linker promotes methyltransferase catalyzed norbornene transfer for rapid bioorthogonal tetrazine ligation

Abstract: Benzylic AdoMet analogs enable highly efficient enzymatic transfer of norbornenes to nucleic acids and subsequent tetrazine ligation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 53 publications
0
31
0
1
Order By: Relevance
“…A cause for this effect may be the enhanced reactivity of benzylic positions towards substitution and the conjugative stabilization of the sp 2 -hybridized S N 2-transition state through the aromatic system, which has recently also been observed for RNA MTases. 28 Irradiating samples of caged duplex ODNI R ÁODNII Me for different time periods at l = 365 nm using a UV hand lamp (6 W) revealed clean and rapid photorelease of uncaged duplex for NB-, 4MNB-and 5MNB-modified ODNI and thus confirmed the reversibility of the enzymatic labelling reaction (Fig. 2d and Fig.…”
mentioning
confidence: 55%
“…A cause for this effect may be the enhanced reactivity of benzylic positions towards substitution and the conjugative stabilization of the sp 2 -hybridized S N 2-transition state through the aromatic system, which has recently also been observed for RNA MTases. 28 Irradiating samples of caged duplex ODNI R ÁODNII Me for different time periods at l = 365 nm using a UV hand lamp (6 W) revealed clean and rapid photorelease of uncaged duplex for NB-, 4MNB-and 5MNB-modified ODNI and thus confirmed the reversibility of the enzymatic labelling reaction (Fig. 2d and Fig.…”
mentioning
confidence: 55%
“…11), as they enabled a fast tetrazine ligation for post-synthetic labeling of DNA and RNA. 147 Lately, AdoMet analogs were also used to modify DNA with photocleavable groups. 148 Two main strategies have been established to label DNA using MTases and fluorophore bearing cofactors.…”
Section: Direct Chemo-enzymatic Labelingmentioning
confidence: 99%
“…Recently, we revealed that the N 7-cap methyltransferase Ecm1 from Encephalitozoon cuniculi is highly promiscuous. Sterically very demanding AdoMet analogues bearing for example a norbornene or 4-vinylbenzyl moiety were efficiently converted [ 92 93 ]. The pronounced promiscuity can be attributed to the structure of Ecm1 which forms a substrate binding cleft rather than a pocket [ 94 ].…”
Section: Reviewmentioning
confidence: 99%